Visual Determination of Copper (II) Using a Biomass Sourced Carbon Quantum Dot (CQD) Ratiometric Fluorescent Probe - Wen, He; Lim, Soh Fong; Rubiyah, Baini; Yanping, Qu; Xiujuan, Lu (Taylor & Francis, 2024)
Accurate detection of copper ions is crucial since it is an essential trace element. Carbon quantum dots (CQDs) were prepared from apricot leaves using a hydrothermal method. These CQDs, which generated a reference signal, were combined with glutathionebound gold nanoclusters (GSH-AuNCs) synthesized by the reduction of chloroauric acid to form a ratiometric fluorescent probe. The probe exhibited fluorescence emission at 450 nm and 568 nm. The determination of Cu(II) was performed through visual analysis of the color change and the intensity ratio (I450/I568) of the emission peaks. Orange fluorescent GSH-AuNCs responded to Cu(II) with fluorescence, and the blue fluorescent CQDs were chemically inert. The probes changed color from pink to purple to blue in response to different concentrations of Cu(II). The linear range of the fluorescence probe for Cu(II) was 0 to 120 mmol/L, and the limit of detection (LOD) was 0.65 mmol/L. This study has demonstrated that the probe provided good selectivity for detecting Cu(II) in water and has potential practical application.